Quantifying the impact of mobile gaming addiction on the quality of life of Malaysian young urban adults / Muhammad Aidil Ab Ghani and Azman Ahmad Tajri - Ab Ghani, Muhammad Aidil; Ahmad Tajri, Azman (Universiti Teknologi MARA, Negeri Sembilan, 2025)
Mobile gaming addiction is increasingly prevalent among young adults, with significant implications for their overall wellbeing. This study investigates the level of mobile gaming addiction in Petaling Jaya, its effects on young adult wellbeing, and the relationship between addiction and wellbeing. The findings aim to offer actionable insights into addressing addiction-related challenges within this demographic. This non-experimental, quantitative study employed questionnaires to measure mobile gaming addiction and its effects on young adult wellbeing. The sample consisted of young adults aged 18 to 24 years, selected through simple random sampling in Petaling Jaya. Data collection focused on the relationship between gaming addiction levels and wellbeing indicators.